Ethnonutrition - Jacob, Michelle Cristine Medeiros; Teixeira, Carla Djaine; Bautista, Danielle Amorim; Ramos, Vanessa Almeida Nogueira (Ethnobiology and Conservation, 2021)
Ethnonutrition, also known as nutritional anthropology and cultural nutrition, is a discipline that studies the diets of different peoples and cultures using a socio-ecological approach. Research in ethnonutrition analyzes the effect of cultural variables in nutritional outcomes under the following topics: (i) sociocultural processes, (ii) social epidemiology, (iii) idea systems, (iv) gene-culture coevolution, (v) food biodiversity. By addressing the cultural bias to which diets are embedded, ethnonutrition science sheds light on how nutrition can (i) promote diets that can contribute to the well-being of people of different cultures, (ii) while protecting all forms of life, and (iii) ensuring the sustainability of the planet.